The [im]possibility of planning a future: how prolonged precarious employment during transitions affects the lives of young Australians. (2nd October 2019) - Cuervo, Hernan; Chesters, Jenny
ABSTRACT: Debates around new patterns of youth transitions to adulthood have been well documented in academic research. In a similar vein, there is an important array of research on the rise of precarious work in labour markets. What has been less well understood is what does precarious employment do to young people in their transitions to adulthood. In this paper, we examine the effects of precarious employment on the present and future lives of young people. We draw on two waves of surveys, in 2012 and 2017, from longitudinal research project tracking a cohort of young Australians over the last decade. We track their employment experiences as they transition into adulthood, paying particular attention to the effects that engagement in precarious employment has on their relationships, wellbeing and their ability to plan for the future. Ultimately, our aim is to contribute to the current debates on this central contemporary concept of social life, precarious work, by interrogating what precarious employment does to young people's lives.